TRANSLATION POLICIES IN LATVIA DURING THE GERMAN OCCUPATION - Veisbergs, Andrejs (Vertimo studijos, 2017)
The period of German occupation in Latvia came after twenty years of Latvian independence and a year of Soviet occupation. The shifts in the translation policies at these critical junctions were incredibly fast. The independence period was marked by a developed translation industry, a variety of the source languages, a variety of kinds of literature, with a broad scope in the quality of the translations. When the Soviets came, they quickly nationalized the publishers, ideologised the system and reshaped the pattern of what was translated. Russian was made the main source language, and other languages were minimized. The share of ideological literature grew exponentially, reaching one third of all books. Soon after the German invasion, the publishers regained their printing houses and publishing was renewed. The percentage of translations was similar to that of the independence period, with German literature making up 70% of the source texts. Most of the other source texts were Nordic and Estonian. Translation quality of fiction was generally high and the print runs grew. There are surprisingly few ideologically motivated translations. The official policies of the regime as regards publishing in Latvia appear to be uncoordinated and vague, with occasional decisions taken by “gate-keepers” in the Ostministerium and other authorities according to their own preferences. There was a nominal pre-censorship, but the publishers were expected to know and sense what was acceptable. In turn the latter played it safe, sticking to classical and serious works to translate and publish. Some high class translations of Latvian classics into German were also published during the period.